A bio-based nylon composite material and preparation method thereof

Through the melt extrusion granulation technology of modified biomass nylon and modified shell powder, biomass nylon composite materials with improved tensile strength, bending strength and impact strength were prepared, solving the problems of carbon emissions and performance improvement of existing biomass nylon products, and achieving high-performance and environmentally friendly biomass nylon composite materials.

CN119350845BActive Publication Date: 2025-04-18DONGYING RUIHUI SYNTHETIC MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411346458.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-04-18
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The monomer preparation of existing bio-based nylon products mainly relies on petroleum-based products, resulting in carbon emissions and resource shortages, and its performance needs to be further improved to meet market demand.

Method used

Through the melt extrusion granulation technology of modified biomass nylon and modified shell powder, a biomass nylon composite material with improved tensile strength, bending strength and impact strength was prepared. This technology includes the use of silane coupling agent to modify shell powder, synthesize bismaleimide monomer and polyhydrogen bond monomer, and form a polymer with self-healing ability.

Benefits of technology

It improves the mechanical strength, high temperature resistance and flame retardant effect of bio-based nylon composite materials, while enhancing its self-repair ability, meeting the market's demand for performance improvement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a bio-based nylon composite material and a preparation method thereof, and relates to the technical field of polymer materials. When preparing the bio-based nylon composite material, the present invention first modifies shell powder with a silane coupling agent to obtain silicon-hydrogen modified shell powder; reacts N-hydroxyethyl maleimide with allyl phosphine dichloride to obtain bismaleimide monomer; reacts bismaleimide monomer with silicon-hydrogen modified shell powder to obtain modified shell powder; reacts dibutyl oxalate with methylguanamine to obtain multi-hydrogen bond monomer; reacts furfurylamine with methyl acrylate to obtain side furanyl dimethyl ester; solid-phase polymerization of side furanyl dimethyl ester, 1,10-decanediamine, and multi-hydrogen bond monomers to obtain modified bio-based nylon; and melt-extrudes and granulates the modified bio-based nylon and the modified shell powder to obtain a bio-based nylon composite material. The bio-based nylon composite material prepared by the present invention has the advantages of high mechanical strength, flame retardancy, self-repairing, and good heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a bio-based nylon composite material and a preparation method thereof. Background Art

[0002] The widespread use of polymer materials has brought great convenience to people's daily lives. However, the raw materials for most synthetic polymers come from petroleum-based chemical products, which are usually accompanied by a large amount of carbon emissions during the production process. The application of bio-based polymers can alleviate the pressure of oil resource shortage and reduce carbon emissions. At present, the bio-based polymer materials that are studied more are mainly bio-based polyesters and bio-based polyamides. With the growth of market demand, more and more bio-based polymers have appeared, showing a trend of diversification, and the market share has also increased year by year.

[0003] As one of the most important engineering plastics, polyamide has been widely used in many fields such as automobiles, electronics and electrical, aerospace, etc. However, the polymerization monomers of most polyamide products are derived from petroleum-based products. Bio-based polyamide has developed rapidly in recent years, and some products have been commercialized.

[0004] Most bio-based nylon products have some or all monomers made from biomass materials or through biological methods. Currently, there are two main routes for monomer preparation, namely the oil route and the sugar route. The oil route is mainly to prepare monomers through chemical reactions such as ester exchange, cracking and hydrolysis, and aminolysis of animal and plant oils. Castor oil is the source of monomers for synthetic bio-based nylon. It is extracted from mature castor seeds. Castor oil is rich in fatty acids and has high economic value. Sebacic acid and 11-aminoundecanoic acid are prepared by this method. Sebacic acid can be further nitrilated, hydrogenated and catalyzed to prepare decanediamine. Sebacic acid and decanediamine are the main raw materials for products such as PA1010, PA1012, and PA610. Summary of the invention

[0005] The purpose of the present invention is to provide a bio-based nylon composite material and a preparation method thereof to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A bio-based nylon composite material, wherein the bio-based nylon composite material is prepared by melt-extrusion granulation of modified bio-based nylon and modified shell powder;

[0008] The modified bio-based nylon is prepared by solid phase polymerization of furanyl dimethyl ester, 1,10-decanediamine and multi-hydrogen bond monomers;

[0009] The multi-hydrogen bond monomer is prepared by reacting dibutyl oxalate with methylguanamine;

[0010] The furanyl dimethyl ester is prepared by reacting furfurylamine with methyl acrylate;

[0011] The modified shell powder is prepared by reacting bismaleimide monomer with silicon hydrogen modified shell powder;

[0012] The silicon-hydrogen modified shell powder is prepared by modifying shell powder with a silane coupling agent;

[0013] The bismaleimide monomer is prepared by reacting N-hydroxyethylmaleimide with allylphosphine dichloride.

[0014] As an optimization, the silane coupling agent is one of trimethoxysilane and triethoxysilane.

[0015] As an optimization, the particle size of the shell powder is 3000 mesh.

[0016] A method for preparing a bio-based nylon composite material comprises the following preparation steps:

[0017] (1) N-hydroxyethylmaleimide, triethylamine and diethylene glycol dimethyl ether are uniformly mixed in a mass ratio of 1:(0.68-0.72):(8-9), and allylphosphine dichloride (0.51-0.56 times the mass of N-hydroxyethylmaleimide) is added dropwise at a rate of 1-2 drops per second under a nitrogen atmosphere, and the temperature is controlled not to exceed 20° C. during the addition process. After the addition is completed, the mixture is reacted in an ice water bath at 300-400 r / min for 5-6 hours, and allowed to stand for 10-12 hours. The mixture is filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a bismaleimide monomer;

[0018] (2) mixing shell powder, pure water and anhydrous ethanol in a mass ratio of 1:(1-2):(9-10) and performing ultrasonic dispersion for 60-80 min, adding modified hydrolyzate in a mass ratio of triethoxysilane to shell powder of 1:(5-6), performing reflux reaction at 70-80° C. and 400-500 r / min for 6-8 h, centrifuging at 4000-5000 rpm for 10-15 min, ultrasonically washing the solid with anhydrous ethanol for 3-5 times, and vacuum drying at 60-70° C. for 12-14 h to obtain silicon-hydrogen modified shell powder;

[0019] (3) Mix the silicon-hydrogen modified shell powder and diethylene glycol dimethyl ether in a mass ratio of 1:(8-9), ultrasonically disperse for 60-80 minutes, add bismaleimide monomer in an amount of 0.2-0.25 times the mass of silicon-hydrogen modified shell powder and chloroplatinic acid in an amount of 0.001-0.0012 times the mass of silicon-hydrogen modified shell powder, stir at 300-400 r / min for 20-30 minutes at room temperature, react at 60-70°C and 300-400 r / min for 4-6 hours, centrifuge at 4000-5000 rpm for 10-15 minutes, collect the precipitated solid, wash with ethanol and pure water alternately, centrifuge for 3 times each, and vacuum dry at 80-90°C for 8-10 hours to obtain modified shell powder;

[0020] (4) mixing furfurylamine and methyl acrylate in a molar ratio of 1:2, reacting at 50°C and 300-400 r / min for 3-4 hours to obtain furanyl dimethyl ester;

[0021] (5) Dibutyl oxalate and petroleum ether are mixed uniformly in a mass ratio of 1:(8-10), stirred at 300-400 r / min for 30-40 min at room temperature, and a 10 wt% methylguanamine petroleum ether solution is added dropwise at a molar ratio of methylguanamine to dibutyl oxalate of 1:(3-4) at 3-4 drops per second. After the addition is completed, react at 300-400 r / min for 5-6 h at room temperature, filter, dry, and purify to obtain a multi-hydrogen bond monomer;

[0022] (6) grinding furanyl dimethyl ester, 1,10-decanediamine, and a multi-hydrogen bond monomer in a molar ratio of (0.8-1.2):(2.05-2.1):(0.8-1.2) and mixing them uniformly, replacing the air with nitrogen three times, and performing solid phase polymerization at 120-150 r / min under a nitrogen atmosphere of 0.2 MPa according to a polymerization heating system, and naturally cooling to room temperature after the polymerization is completed to obtain a modified bio-based nylon;

[0023] (7) The modified bio-based nylon and the modified shell powder were uniformly mixed in a high-speed mixer at a mass ratio of 1:(0.05-0.1), and granulated by extrusion at 290-310°C and 400-600 r / min using a twin-screw extruder. After drying in a drying oven at 110°C for 2 h, a bio-based nylon composite material was obtained.

[0024] As an optimization, the reaction process of the bismaleimide monomer in step (1) is as follows:

[0025]

[0026] As an optimization, the modified hydrolyzate in step (2) is prepared by uniformly mixing triethoxysilane, pure water and anhydrous ethanol in a mass ratio of 1:(1.1-1.2):(9-10), and stirring at 50-60° C. and 300-400 r / min for 1 hour.

[0027] As an optimization, the reaction process of the modified shell powder in step (3) is as follows:

[0028]

[0029] As an optimization, the reaction process of the furanyl dimethyl ester in step (4) is as follows:

[0030]

[0031] As an optimization, the multi-hydrogen bond monomer reaction process in step (5) is as follows:

[0032]

[0033] As an optimization, the polymerization temperature rising system in step (6) is to first increase the temperature to 120°C at a heating rate of 5°C / min and maintain for 1 hour; then increase the temperature to 140°C at a heating rate of 2°C / min and maintain for 30 minutes, keep the temperature for 30 minutes at each heating of 20°C, raise the temperature to 200°C, release the pressure and start vacuuming, reduce the vacuum degree to below 100 Pa, increase the temperature to 250-260°C at 5°C / min, maintain for 1-1.5 hours, and then increase the temperature to 300°C and maintain for 45-55 minutes.

[0034] As an optimization, the reaction process of modified bio-based nylon in step (6) is as follows:

[0035]

[0036] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0037] When preparing the bio-based nylon composite material, the present invention first uses a silane coupling agent to modify shell powder to obtain silicon-hydrogen modified shell powder; N-hydroxyethyl maleimide is reacted with allyl phosphine dichloride to obtain bismaleimide monomer; the bismaleimide monomer is reacted with silicon-hydrogen modified shell powder to obtain modified shell powder; dibutyl oxalate is reacted with methylguanamine to obtain a multi-hydrogen bond monomer; furfurylamine is reacted with methyl acrylate to obtain side furanyl dimethyl ester; side furanyl dimethyl ester, 1,10-decanediamine and multi-hydrogen bond monomer are solid-phase polymerized to obtain modified bio-based nylon; the modified bio-based nylon and the modified shell powder are melt-extruded and granulated to obtain the bio-based nylon composite material.

[0038] Firstly, the shell powder is modified by a silane coupling agent containing silicon-hydrogen bonds, and silicon-hydrogen bonds are introduced into the surface of the shell powder; N-hydroxyethylmaleimide reacts with allyl phosphine dichloride to prepare a bismaleimide monomer containing a double bond, a bismaleimide group and a phosphorus element. The double bond can undergo a silylation reaction with the silicon-hydrogen bonds on the surface of the silicon-hydrogen modified shell powder, and the bismaleimide monomer is grafted onto the surface of the silicon-hydrogen modified shell powder. The bismaleimide group participates in the subsequent reversible DA reaction with the furan group on the polyamide main chain, thereby improving the self-healing ability of the bio-based nylon composite material and improving the tensile strength, flexural strength and impact strength; the introduction of the phosphorus element synergizes with the nitrogen element to achieve flame retardancy and enhance the flame retardant effect.

[0039] Secondly, the multi-hydrogen bond monomer obtained by the reaction of dibutyl oxalate and methylguanamine can form quadruple hydrogen bonds. The introduction of multiple hydrogen bonds improves the self-healing ability of bio-based nylon composites, improves its high temperature resistance, and improves the mechanical strength. Methylguanamine contains a high content of nitrogen and can also produce a synergistic flame retardant effect with the phosphorus element on the modified shell powder, thereby enhancing the flame retardant effect. Furfurylamine and methyl acrylate undergo Michael addition reaction to obtain side furanyl dimethyl ester, introduce furan groups into the polyamide main chain, and undergo reversible DA reaction with the bismaleimide groups on the modified shell powder.

[0040] Finally, modified bio-based nylon was prepared by solid phase polymerization of furanyl dimethyl ester, 1,10-decanediamine and multi-hydrogen bond monomer, and melt extrusion granulation with modified shell powder prepared bio-based nylon composites. The melt blending of modified shell powder and modified bio-based nylon effectively improved the mechanical strength of the bio-based nylon composite. At the same time, the bismaleimide group on the modified shell powder can also react with the furan group on the modified bio-based nylon to undergo DA reaction, thereby improving the dispersibility and compatibility of the modified shell powder in the bio-based nylon composite. DETAILED DESCRIPTION

[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] The following articles and comparative examples are provided with information or preparation methods as follows:

[0043] Modified hydrolyzate: triethoxysilane, pure water and anhydrous ethanol were mixed evenly in a mass ratio of 1:1.1:10, and stirred at 60°C and 350 r / min for 1 h to prepare the modified hydrolyzate;

[0044] Shell powder: particle size is 3000 mesh, brand is Yiteng, whiteness is 96.

[0045] The polymerization heating system used in the following embodiments and comparative examples is as follows: first, the temperature is raised to 120°C at a heating rate of 5°C / min and maintained for 1h; then, the temperature is raised to 140°C at a heating rate of 2°C / min and maintained for 30min, and the temperature is kept for 30min at each heating of 20°C, and the temperature is raised to 200°C. After the pressure is released, vacuum is started to be drawn to below 100Pa, and the temperature is raised to 250°C at 5°C / min, maintained for 1h, and then raised to 300°C and maintained for 55min.

[0046] Embodiment 1:

[0047] A method for preparing a bio-based nylon composite material, the method for preparing the bio-based nylon composite material comprising the following preparation steps:

[0048] (1) N-hydroxyethylmaleimide, triethylamine, and diethylene glycol dimethyl ether are mixed uniformly in a mass ratio of 1:0.68:8, and allylphosphine dichloride (0.51 times the mass of N-hydroxyethylmaleimide) is added dropwise at a rate of 1 drop per second under a nitrogen atmosphere, and the temperature is controlled not to exceed 20° C. during the addition process. After the addition is completed, the mixture is reacted in an ice water bath at 300 r / min for 5 h, allowed to stand for 10 h, filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a bismaleimide monomer;

[0049] (2) Mix shell powder, pure water and anhydrous ethanol in a mass ratio of 1:1:9, ultrasonically disperse for 60 minutes, add modified hydrolyzate in a mass ratio of triethoxysilane to shell powder of 1:5, reflux at 70°C and 400 r / min for 6 hours, centrifuge at 4000 rpm for 15 minutes, ultrasonically clean the solid three times with anhydrous ethanol, and vacuum dry at 60°C for 14 hours to obtain silicon-hydrogen modified shell powder;

[0050] (3) The silanol-modified shell powder and diethylene glycol dimethyl ether were mixed uniformly in a mass ratio of 1:8, ultrasonically dispersed for 60 minutes, 0.2 times the mass of bismaleimide monomer of the silanol-modified shell powder and 0.001 times the mass of chloroplatinic acid of the silanol-modified shell powder were added, stirred at 300 r / min for 30 minutes at room temperature, reacted at 60°C and 300 r / min for 6 hours, centrifuged at 4000 rpm for 15 minutes, collected the precipitated solid, washed alternately with ethanol and pure water, centrifuged 3 times each, and vacuum dried at 80°C for 10 hours to obtain modified shell powder;

[0051] (4) mixing furfurylamine and methyl acrylate in a molar ratio of 1:2, reacting at 50° C. and 300 r / min for 4 h to obtain furanyl dimethyl ester;

[0052] (5) Dibutyl oxalate and petroleum ether are mixed in a mass ratio of 1:8, stirred at 300 r / min for 40 min at room temperature, and a 10 wt % methylguanamine petroleum ether solution is added dropwise at a molar ratio of methylguanamine to dibutyl oxalate of 1:3 at 3 drops per second. After the addition is completed, react at 300 r / min for 6 h at room temperature, filter, dry, and purify to obtain a multi-hydrogen bond monomer;

[0053] (6) Grinding furanyl dimethyl ester, 1,10-decanediamine, and a multi-hydrogen bond monomer in a molar ratio of 0.8:2.05:1.2 and mixing them evenly, replacing the air with nitrogen three times, and then performing solid phase polymerization at 120 r / min under a nitrogen atmosphere of 0.2 MPa according to a polymerization heating system. After the polymerization is completed, the mixture is naturally cooled to room temperature to obtain a modified bio-based nylon;

[0054] (7) The modified bio-based nylon and modified shell powder were uniformly mixed in a high-speed mixer at a mass ratio of 1:0.05, and granulated using a twin-screw extruder at 290°C and 400 r / min. After drying in a drying oven at 110°C for 2 h, a bio-based nylon composite material was obtained.

[0055] Embodiment 2:

[0056] A method for preparing a bio-based nylon composite material, the method for preparing the bio-based nylon composite material comprising the following preparation steps:

[0057] (1) N-hydroxyethylmaleimide, triethylamine, and diethylene glycol dimethyl ether are mixed uniformly in a mass ratio of 1:0.7:8.5, and allylphosphine dichloride (0.53 times the mass of N-hydroxyethylmaleimide) is added dropwise at a rate of 2 drops per second under a nitrogen atmosphere, and the temperature is controlled not to exceed 20° C. during the addition process. After the addition is completed, the mixture is reacted in an ice water bath at 350 r / min for 5.5 hours, allowed to stand for 11 hours, filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a bismaleimide monomer;

[0058] (2) Mix shell powder, pure water and anhydrous ethanol in a mass ratio of 1:1.5:9.5, ultrasonically disperse for 70 minutes, add modified hydrolyzate in a mass ratio of triethoxysilane to shell powder of 1:5.5, reflux at 75°C and 450r / min for 7 hours, centrifuge at 4500rpm for 12 minutes, ultrasonically clean the solid 4 times with anhydrous ethanol, and vacuum dry at 65°C for 13 hours to obtain silicon-hydrogen modified shell powder;

[0059] (3) The silane-modified shell powder and diethylene glycol dimethyl ether were mixed uniformly in a mass ratio of 1:8.5, ultrasonically dispersed for 7 minutes, added bismaleimide monomer (0.22 times the mass of the silane-modified shell powder) and chloroplatinic acid (0.0011 times the mass of the silane-modified shell powder), stirred at 350 r / min for 25 minutes at room temperature, reacted at 65°C and 350 r / min for 5 hours, centrifuged at 4500 rpm for 12 minutes, collected the precipitated solid, washed alternately with ethanol and pure water, centrifuged 3 times each, and vacuum dried at 85°C for 9 hours to obtain the modified shell powder;

[0060] (4) mixing furfurylamine and methyl acrylate in a molar ratio of 1:2, and reacting at 50° C. and 350 r / min for 3.5 h to obtain furanyl dimethyl ester;

[0061] (5) Dibutyl oxalate and petroleum ether were mixed in a mass ratio of 1:9, stirred at 350 r / min for 35 min at room temperature, and a 10 wt % methylguanamine petroleum ether solution was added dropwise at a molar ratio of methylguanamine to dibutyl oxalate of 1:3.5 at 3 drops per second. After the addition was completed, the mixture was reacted at 350 r / min for 5.5 h at room temperature, filtered, dried, and purified to obtain a multi-hydrogen bond monomer;

[0062] (6) Grinding furanyl dimethyl ester, 1,10-decanediamine, and a multi-hydrogen bond monomer in a molar ratio of 1:2.08:1 and mixing them uniformly, replacing the air with nitrogen three times, and then performing solid phase polymerization at 150 r / min under a nitrogen atmosphere of 0.2 MPa according to a polymerization heating system. After the polymerization is completed, the mixture is naturally cooled to room temperature to obtain a modified bio-based nylon;

[0063] (7) The modified bio-based nylon and modified shell powder were uniformly mixed in a high-speed mixer at a mass ratio of 1:0.08, and granulated by extrusion at 300°C and 500 r / min using a twin-screw extruder. After drying in a drying oven at 110°C for 2 h, a bio-based nylon composite material was obtained.

[0064] Embodiment 3:

[0065] A method for preparing a bio-based nylon composite material, the method for preparing the bio-based nylon composite material comprising the following preparation steps:

[0066] (1) N-hydroxyethylmaleimide, triethylamine, and diethylene glycol dimethyl ether are mixed uniformly in a mass ratio of 1:0.72:9, and allylphosphine dichloride (0.56 times the mass of N-hydroxyethylmaleimide) is added dropwise at a rate of 2 drops per second under a nitrogen atmosphere, and the temperature is controlled not to exceed 20° C. during the addition process. After the addition is completed, the mixture is reacted at 400 r / min in an ice water bath for 5 hours, allowed to stand for 12 hours, filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a bismaleimide monomer;

[0067] (2) Mix shell powder, pure water and anhydrous ethanol in a mass ratio of 1:2:10, ultrasonically disperse for 80 minutes, add modified hydrolyzate in a mass ratio of triethoxysilane to shell powder of 1:6, reflux at 80°C and 500 r / min for 8 hours, centrifuge at 5000 rpm for 10 minutes, ultrasonically clean the solid with anhydrous ethanol for 5 times, and vacuum dry at 70°C for 12 hours to obtain silicon-hydrogen modified shell powder;

[0068] (3) The silanol-modified shell powder and diethylene glycol dimethyl ether were mixed uniformly in a mass ratio of 1:9, ultrasonically dispersed for 80 minutes, 0.25 times the mass of bismaleimide monomer of the silanol-modified shell powder and 0.0012 times the mass of chloroplatinic acid of the silanol-modified shell powder were added, stirred at 400 r / min for 20 minutes at room temperature, reacted at 70°C and 400 r / min for 4 hours, centrifuged at 5000 rpm for 10 minutes, collected the precipitated solid, washed alternately with ethanol and pure water, centrifuged 3 times each, and vacuum dried at 90°C for 8 hours to obtain modified shell powder;

[0069] (4) mixing furfurylamine and methyl acrylate in a molar ratio of 1:2, and reacting at 50° C. and 400 r / min for 3 h to obtain furanyl dimethyl ester;

[0070] (5) Dibutyl oxalate and petroleum ether are mixed in a mass ratio of 1:10, stirred at 400 r / min for 30 min at room temperature, and a 10 wt % methylguanamine petroleum ether solution is added dropwise at a rate of 4 drops per second, with a molar ratio of methylguanamine to dibutyl oxalate of 1:4. After the addition is completed, react at room temperature at 400 r / min for 5 h, filter, dry, and purify to obtain a multi-hydrogen bond monomer;

[0071] (6) Grinding furanyl dimethyl ester, 1,10-decanediamine, and a multi-hydrogen bond monomer in a molar ratio of 1.2:2.1:0.8 and mixing them uniformly, replacing the air with nitrogen three times, and then performing solid phase polymerization at 150 r / min under a nitrogen atmosphere of 0.2 MPa according to a polymerization heating system. After the polymerization is completed, the mixture is naturally cooled to room temperature to obtain a modified bio-based nylon;

[0072] (7) The modified bio-based nylon and modified shell powder were uniformly mixed in a high-speed mixer at a mass ratio of 1:0.1, and granulated using a twin-screw extruder at 310°C and 600 r / min. After drying in a drying oven at 110°C for 2 h, a bio-based nylon composite material was obtained.

[0073] Comparative Example 1:

[0074] The preparation method of the bio-based nylon composite material of Comparative Example 1 is different from that of Example 2 in that steps (1) and (3) are not performed, and step (7) is modified as follows: the modified bio-based nylon and the silicon-hydrogen modified shell powder are uniformly mixed in a high-speed mixer at a mass ratio of 1:0.08, extruded and granulated using a twin-screw extruder at 300° C. and 500 r / min, and dried in a drying oven at 110° C. for 2 h to obtain a bio-based nylon composite material. The remaining steps are the same as those of Example 2.

[0075] Comparative Example 2:

[0076] The preparation method of the bio-based nylon composite material of Comparative Example 2 is different from that of Example 2 in that steps (1), (2) and (3) are not performed, and step (7) is modified as follows: the modified bio-based nylon is extruded and granulated using a twin-screw extruder at 300° C. and 500 r / min, and dried in a drying oven at 110° C. for 2 h to obtain a bio-based nylon composite material. The remaining steps are the same as those of Example 2.

[0077] Comparative Example 3:

[0078] The preparation method of the bio-based nylon composite material of Comparative Example 3 is different from that of Example 2 in that step (4) is not performed, and step (6) is modified as follows: 1,10-decanediamine and a multi-hydrogen bond monomer are ground and mixed evenly in a molar ratio of 2.08:2, and the air is replaced with nitrogen three times, and solid phase polymerization is performed at 150 r / min under a nitrogen atmosphere of 0.2 MPa according to a polymerization heating system, and naturally cooled to room temperature after the polymerization is completed to obtain modified bio-based nylon. The remaining steps are the same as those of Example 2.

[0079] Comparative Example 4:

[0080] The preparation method of the bio-based nylon composite material of Comparative Example 4 is different from that of Example 2 in that step (5) is not performed, and step (6) is modified as follows: the side furanyl dimethyl ester and 1,10-decanediamine are ground and mixed evenly in a molar ratio of 2:2.08, the air is replaced with nitrogen three times, and solid phase polymerization is performed at 150r / min under a nitrogen atmosphere of 0.2MPa according to a polymerization heating system, and naturally cooled to room temperature after the polymerization is completed to obtain modified bio-based nylon. The remaining steps are the same as those of Example 2.

[0081] Comparative Example 5:

[0082] The preparation method of the bio-based nylon composite material of Comparative Example 5 is different from that of Example 2 in step (5), and step (5) is modified as follows: dibutyl oxalate and petroleum ether are mixed uniformly in a mass ratio of 1:9, stirred at room temperature at 350r / min for 35min, 10wt% 1,5-pentanediamine petroleum ether solution is added dropwise at 3 drops per second, and the molar ratio of 1,5-pentanediamine to dibutyl oxalate is 1:3.5. After the addition is completed, react at room temperature at 350r / min for 5.5h, filter, dry, and purify to obtain a multi-hydrogen bond monomer. The remaining steps are the same as those of Example 2.

[0083] The bio-based nylon composite materials prepared in the above examples and comparative examples were injection molded at 330° C. according to the test requirements of each test example to prepare corresponding standard specimens for testing.

[0084] Test Example 1:

[0085] Mechanical properties test: The tensile strength, flexural strength and impact strength were tested to evaluate the mechanical properties of the prepared bio-based nylon composite material. The specific test methods are as follows:

[0086] Tensile strength test: refer to GB / T 1040.2-2022 for the tensile strength test. The sample shape is 1A type sample. Each group of 5 samples is tested and the average value is recorded.

[0087] Bending strength test: refer to GB / T 9341-2008 for the bending strength test, and test 5 samples in each group and take the average value for recording;

[0088] Impact strength test: refer to GB / T 1043.1-2008 for notched impact strength test, use dynamic impact analyzer, the notch shape of the sample adopts C-notch, the test is carried out at room temperature, and 5 samples are tested in each group to take the average value and record.

[0089] The results are shown in Table 1.

[0090] Table 1

[0091] Tensile strength / MPa Bending strength / MPa <![CDATA[Impact strength / KJ·m -2 > Example 1 105.4 91.5 56.3 Example 2 106.8 92.4 58.5 Example 3 104.7 90.8 57.1 Comparative Example 1 91.5 77.3 43.2 Comparative Example 2 75.2 56.4 24.3 Comparative Example 3 88.6 75.2 44.8 Comparative Example 4 81.5 63.4 32.6 Comparative Example 5 88.9 72.6 39.7

[0092] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the bio-based nylon composite material prepared by the present invention has good tensile strength, flexural strength and impact strength.

[0093] Comparison of the data in the table shows that maleimide and furan ring undergo DA reaction, which effectively improves the mechanical strength. At the same time, the addition of modified shell powder improves the crystallization performance and effectively improves the mechanical strength. The introduction of multi-hydrogen bond monomers can form a quadruple hydrogen bond structure, and the triazine ring therein is a rigid structure, which also has an effect on improving the mechanical strength. When methylguanamine is replaced by 1,5-pentanediamine, only double hydrogen bonds can be formed between the molecular chains, the bonding effect is weakened, and the triazine rigid structure is lost, and the mechanical strength is reduced.

[0094] Test Example 2:

[0095] Flame retardant performance test: The limiting oxygen index and UL 94 combustion grade of the prepared bio-based nylon composite material were tested to evaluate its flame retardant effect. The specific test method is as follows:

[0096] Limiting oxygen index test: According to GB / T 2406.1-2008, the limiting oxygen index of the embodiment and the comparative example was tested with an oxygen index instrument, the sample size was 150mm×10mm×3mm, and 5 samples were tested in each group to obtain the average value for recording;

[0097] Vertical combustion test: According to ASTM D3801-2010, the test was carried out using a vertical-horizontal combustion tester, and 5 samples were tested in each group and the average value was recorded.

[0098] The results are shown in Table 2.

[0099] Table 2

[0100] Limiting oxygen index UL 94 rating Example 1 42.1% V-0 Example 2 43.5% V-0 Example 3 41.9% V-0 Comparative Example 1 29.4% V-2 Comparative Example 2 27.5% V-2 Comparative Example 3 40.5% V-0 Comparative Example 4 34.6% V-1 Comparative Example 5 35.4% V-1

[0101] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the bio-based nylon composite material prepared in the present invention has good flame retardant properties.

[0102] By comparing the data in the table, it can be seen that the phosphorus element on the modified shell powder and the high-content nitrogen element on the multi-hydrogen bond monomer form a good synergistic flame retardant effect, which effectively improves the flame retardant properties.

[0103] Test Example 3:

[0104] High temperature resistance test: Use TG 209 thermogravimetric analyzer produced by NETZSCH Instrument Manufacturing Co., Ltd. to test the thermal weight loss of the sample; take 1-5 mg of the sample into a crucible, purge with nitrogen, test the temperature at 25-900°C, and the heating rate at 20°C / min. Record the 5% thermal decomposition temperature. Test 5 samples in each group and take the average value.

[0105] The results are shown in Table 3.

[0106] Table 3

[0107] 5% thermal decomposition temperature / ℃ 5% thermal decomposition temperature / ℃ Example 1 435 Comparative Example 1 421 Example 2 437 Comparative Example 2 404 Example 3 434 Comparative Example 3 422 Comparative Example 4 398 Comparative Example 5 418

[0108] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the bio-based nylon composite material prepared by the present invention has good high temperature resistance.

[0109] By comparing the data in the table, it is shown that the addition of modified shell powder and the DA reaction between maleimide on the modified shell powder and furan can improve the high temperature resistance. At the same time, the multiple hydrogen bond structure formed by dibutyl oxalate and methylguanamine can also effectively improve the high temperature resistance. Even if methylguanamine is replaced by 1,5-pentanediamine, a double hydrogen bond structure can be formed, which can also improve the high temperature resistance.

[0110] Test Example 4:

[0111] Self-healing performance test: The prepared bio-based nylon composite material was made into a tensile strength specimen, and a scalpel was used to cut scratches on the surface of the specimen and mark them. The depth was about 1 mm. The scratch width was measured and recorded using a PTS-E40 comprehensive crack width gauge. The scratched specimen was repaired at 120°C for 12 hours, and the scratch width was measured and recorded again. The remaining scratch width ratio was recorded, and then the scratch width was measured every hour of repair until it was zero. The complete repair time was recorded, and the completely repaired specimen was left to stand at room temperature for 2 days. The tensile strength was then tested according to the tensile strength test method and the repair efficiency was calculated by comparing it with the tensile strength measured in Test Example 1. Five specimens were tested in each group and the average value was recorded.

[0112] The results are shown in Table 4.

[0113] Table 4

[0114]

[0115]

[0116] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the bio-based nylon composite material prepared by the present invention has good self-repairing performance.

[0117] By comparing the data in the table, it is shown that the maleimide group on the modified shell powder reacted with the furan ring on the modified bio-based nylon to undergo a DA reaction, which effectively repaired scratches and cracks at a reversible temperature. The quadruple hydrogen bond structure formed by the multi-hydrogen bond monomer also has a good self-repairing effect, and the multiple hydrogen bond structure and the reversible DA structure have a synergistic self-repairing effect, which effectively improves the repair efficiency and reduces the repair time. After replacing methylguanamine with 1,5-pentanediamine, the repair effect of the molecular chain with only a double hydrogen bond structure is significantly reduced, and it is difficult to achieve the repair effect of the quadruple hydrogen bond.

[0118] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A bio-based nylon composite material, characterized in that: The bio-based nylon composite material is prepared by melt-extruding and granulating modified bio-based nylon and modified shell powder; The modified bio-based nylon is prepared by solid phase polymerization of furanyl dimethyl ester, 1,10-decanediamine and multi-hydrogen bond monomers; The multi-hydrogen bond monomer is prepared by reacting dibutyl oxalate with methylguanamine; The furanyl dimethyl ester is prepared by reacting furfurylamine with methyl acrylate; The modified shell powder is prepared by reacting bismaleimide monomer with silicon hydrogen modified shell powder; The silicon-hydrogen modified shell powder is prepared by modifying shell powder with a silane coupling agent; The bismaleimide monomer is prepared by reacting N-hydroxyethylmaleimide with allylphosphine dichloride.

2. The bio-based nylon composite material according to claim 1, characterized in that: The silane coupling agent is one of trimethoxysilane and triethoxysilane.

3. The bio-based nylon composite material according to claim 1, characterized in that: The particle size of the shell powder is 3000 mesh.

4. A method for preparing a bio-based nylon composite material, characterized in that: The method comprises the following preparation steps: (1) N-hydroxyethylmaleimide, triethylamine and diethylene glycol dimethyl ether are uniformly mixed in a mass ratio of 1:(0.68-0.72):(8-9), and allylphosphine dichloride (0.51-0.56 times the mass of N-hydroxyethylmaleimide) is added dropwise at a rate of 1-2 drops per second under a nitrogen atmosphere, and the temperature is controlled not to exceed 20° C. during the addition process. After the addition is completed, the mixture is reacted in an ice water bath at 300-400 r / min for 5-6 hours, and allowed to stand for 10-12 hours. The mixture is filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a bismaleimide monomer; (2) mixing shell powder, pure water and anhydrous ethanol in a mass ratio of 1:(1-2):(9-10) and performing ultrasonic dispersion for 60-80 min, adding modified hydrolyzate in a mass ratio of triethoxysilane to shell powder of 1:(5-6), performing reflux reaction at 70-80° C. and 400-500 r / min for 6-8 h, centrifuging at 4000-5000 rpm for 10-15 min, ultrasonically washing the solid with anhydrous ethanol for 3-5 times, and vacuum drying at 60-70° C. for 12-14 h to obtain silicon-hydrogen modified shell powder; (3) Mix the silicon-hydrogen modified shell powder and diethylene glycol dimethyl ether in a mass ratio of 1:(8-9), ultrasonically disperse for 60-80 minutes, add bismaleimide monomer in an amount of 0.2-0.25 times the mass of silicon-hydrogen modified shell powder and chloroplatinic acid in an amount of 0.001-0.0012 times the mass of silicon-hydrogen modified shell powder, stir at 300-400 r / min for 20-30 minutes at room temperature, react at 60-70°C and 300-400 r / min for 4-6 hours, centrifuge at 4000-5000 rpm for 10-15 minutes, collect the precipitated solid, wash with ethanol and pure water alternately, centrifuge for 3 times each, and vacuum dry at 80-90°C for 8-10 hours to obtain modified shell powder; (4) mixing furfurylamine and methyl acrylate in a molar ratio of 1:2, reacting at 50°C and 300-400 r / min for 3-4 hours to obtain furanyl dimethyl ester; (5) Dibutyl oxalate and petroleum ether are mixed uniformly in a mass ratio of 1:(8-10), stirred at 300-400 r / min for 30-40 min at room temperature, and a 10 wt% methylguanamine petroleum ether solution is added dropwise at a molar ratio of methylguanamine to dibutyl oxalate of 1:(3-4) at 3-4 drops per second. After the addition is completed, react at 300-400 r / min for 5-6 h at room temperature, filter, dry, and purify to obtain a multi-hydrogen bond monomer; (6) grinding furanyl dimethyl ester, 1,10-decanediamine, and a multi-hydrogen bond monomer in a molar ratio of (0.8-1.2):(2.05-2.1):(0.8-1.2) and mixing them uniformly, replacing the air with nitrogen three times, and performing solid phase polymerization at 120-150 r / min under a nitrogen atmosphere of 0.2 MPa according to a polymerization heating system, and naturally cooling to room temperature after the polymerization is completed to obtain a modified bio-based nylon; (7) The modified bio-based nylon and the modified shell powder were uniformly mixed in a high-speed mixer at a mass ratio of 1:(0.05-0.1), and granulated by extrusion at 290-310°C and 400-600 r / min using a twin-screw extruder. After drying in a drying oven at 110°C for 2 h, a bio-based nylon composite material was obtained.

5. The method for preparing a bio-based nylon composite material according to claim 4, characterized in that: The modified hydrolyzate in step (2) is prepared by uniformly mixing triethoxysilane, pure water and anhydrous ethanol in a mass ratio of 1:(1.1-1.2):(9-10), and stirring at 50-60° C. and 300-400 r / min for 1 hour.

6. The method for preparing a bio-based nylon composite material according to claim 4, characterized in that: The polymerization temperature rise system in step (6) is to first increase the temperature to 120°C at a heating rate of 5°C / min and maintain for 1 hour; then increase the temperature to 140°C at a heating rate of 2°C / min and maintain for 30 minutes, and keep the temperature for 30 minutes at each heating of 20°C, raise the temperature to 200°C, release the pressure and start vacuuming, reduce the vacuum degree to below 100 Pa, increase the temperature to 250-260°C at 5°C / min, maintain for 1-1.5 hours, and then increase the temperature to 300°C and maintain for 45-55 minutes.

Citation Information

Patent Citations

  • Shell powder modified decorative nylon material and preparation method thereof

    CN108084705A

  • Nylon biomass composite material and preparation method thereof

    CN113004686A